Manutenção da prática de atividade física e indicadores hemodinâmicos, metabólicos e inflamatório em adultos: análise transversal e coorte de 12 meses - Lima, Manoel Carlos Spiguel [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Aim: (i) to compare blood flow and mediointimal thickness indicators between active and sedentary adults throughout life, as well as, (ii) to analyze the relationship between these variables (adjusted by lipid profile, inflammatory indicator and behavioral variables) after a follow-up of 12 months. Methods: A cross-sectional and a cohort study of 12 months were carried out with at least 96 individuals of both sexes. All of the potential participants selected were put in to the experiment or apply in the established inclusion criteria: (i) persistently active (active in childhood, adolescence and currently physically active in leisure) or persistently sedentary (inactive in childhood, adolescence and currently sedentary in leisure), (ii) age between 30 and 50 years old, (iii) no previous history of brain stroke or heart attack, (iv) no amputation or visual problem due to diabetes mellitus. The sample was subdivided in two groups (persistently active, persistently inactive), which were paired by sex, ethnic and age (30-39 years / 40-50 years). Initially, the experiment was composed by three questionnaires (an anamnesis [history of illness, medication use, dietary habits, smoking and alcohol habits], sleep quality and current physical activity in leisure, work and locomotion). All participants have been measured: (i) anthropometry (body weight, height and waist circumference), (ii) estimation of body composition (dual-energy X-ray absorptiometry), (iii) pedometer (used for the period of seven days, which was fixed in waist high and only removed during sleep and shower), (iv) blood pressure, rest heart rate and heart rate variability, (v) blood sample for biochemistry analysis (triglycerides, total cholesterol, high density lipoprotein, low density lipoprotein, very low density lipoprotein, glucose, insulin and C-reactive protein ultrasensitive) and (vi) image exam of ultrasonography with Doppler of common carotid and femoral arteries to obtain..

Objetivo: (i) comparar indicadores de fluxo sanguíneo e espessura mediointimal entre adultos ativos e sedentários ao longo da vida, bem como, (ii) analisar a relação entre estas variáveis (ajustada por perfil lipídico, indicador inflamatório e variáveis comportamentais) após um seguimento de 12 meses. Métodos: Foi realizado um estudo transversal e, posteriormente, uma coorte de 12 meses com ao menos 96 indivíduos de ambos os sexos. Todos os potenciais participantes selecionados foram inseridos no experimento ao se enquadrarem nos critérios de inclusão estabelecidos: (i) persistentemente ativo (ativo na infância, na adolescência e atualmente fisicamente ativo no lazer) ou persistentemente sedentário (inativo na infância, na adolescência e atualmente sedentário no lazer); (ii) idade compreendida entre 30 e 50 anos; (iii) sem histórico prévio de acidente vascular cerebral ou infarto; (iv) sem amputação ou problema visual decorrente do diabetes mellitus. A amostra foi subdivida em dois grupos (persistentemente ativos e persistentemente sedentários), os quais foram pareados por sexo, etnia e idade (30 a 39 anos/ 40 a 50 anos). Inicialmente, o experimento foi composto por três questionários (uma anamnese [histórico de doenças, uso de medicamentos, hábitos alimentares, hábitos de fumo e álcool], qualidade do sono e atividade física atual praticada no lazer, trabalho e locomoção). Em todos os participantes foram mensurados: (i) antropometria (peso corporal, estatura e circunferência de cintura), (ii) estimativa da composição corporal (absortometria radiológica de dupla energia), (iii) pedometria (utilizado por um período de sete dias, o qual foi fixado na altura da cintura e somente retirado nas horas de sono e durante o banho), (iv) pressão arterial, frequência cardíaca em repouso e variabilidade da frequência cardíaca, (v) amostra de sangue para análise bioquímica (triacilglicerol, colesterol total....
Keywords: Physical education and trainning; Educação fisica; Exercícios físicos; Hemodinâmica; Inflamação; Doppler, Ultrassonografia; Indicadores (Biologia); Metabolismo; Fluxo sanguineo; Arteriosclerose; Proteína C-Reativa